Pengaruh Metode Latihan Bangsbo Sprint Terhadap Kelincahan Pemain Sepakbola - Iqbal Fajarullah; Debi Krisna Irawan; Irpan Abdurahman; Chaerul Umam Ramadhan (Departement of Mathematics Education, 2023)
There was a lack of scientific investigations conducted concerning the effectiveness of agility training with generic or specific exercises. The purpose of this study was to determine the effect of Bangsbo Sprint training program on agility football players. This study used a pre-experimental method with one group pretest-posttest research design. The population is 38 athletes with using randomly assigned techniques to get 20 UPI football players. Twenty football payers (age: 20.2±1.1 years; height: 165.9±7.6 cm; body mass: 64.5±0.7 kg, body fat: 11.5±0.7%) participated in a short-term (16 meetings in 2 months) training study. The research instrument used the Illinois Agility Test. There is a significant effect of the Bangsbo Sprint training program on increasing agility. Based on the results of data analysis, there are an average pretest 17.40±0.34 seconds, then the treatment was conducted for 16 meetings and there was an average posttest result 17.03±0.49 seconds, the agility performance was significantly increased from pre-post training. In conclusion, the Bangsbo Sprint training program has a significant effect on improving the agility of UPI Bandung football players.